European Bat Lyssavirus Infection in Spanish Bat Populations - Serra-Cobo, Jordi (Centers for Disease Control and Prevention, 2002)
From 1992 to 2000, 976 sera, 27 blood pellets, and 91 brains were obtained from 14 bat species in 37 localities in Spain. Specific anti-European bat lyssavirus 1 (EBL1)-neutralizing antibodies have been detected in Myotis myotis, Miniopterus schreibersii, Tadarida teniotis, and Rhinolophus ferrumequinum in the region of Aragon and the Balearic Islands. Positive results were also obtained by nested reverse transcription-polymerase chain reaction on brain, blood pellet, lung, heart, tongue, and esophagus-larynx-pharynx of M. myotis, Myotis nattereri, R. ferrumequinum, and M. schreibersii. Determination of nucleotide sequence confirmed the presence of EBL1 RNA in the different tissues. In one colony, the prevalence of seropositive bats over time corresponded to an asymmetrical curve, with a sudden initial increase peaking at 60% of the bats, followed by a gradual decline. Banded seropositive bats were recovered during several years, indicating that EBL1 infection in these bats was nonlethal. At least one of this species (M. schreibersii) is migratory and thus could be partially responsible for the dissemination of EBL1 on both shores of the Mediterranean Sea.